Peradaban Islam Masa Utsman Bin Affan - Mia Safitri; Novita Angerani; Septi Paremadona; Septiwi Annisa Putri; Suciati Suciati; Rafidi Rafidi; Dwi Noviani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Islamic civilization during the time of Uthman bin Affan was an important chapter in Islamic history which marked the rapid development and broad influence of the Muslim Ummah. Uthman bin Affan, as the third caliph in Islamic history, led the Muslim community in the period 644-656 AD. His reign was marked by the expansion of Islamic territory, economic stability, and the writing of the Koran which was compiled in a standard form. Uthman's reign also saw the development of science, art, and architecture. Increased trade activity and relations with various nations and cultures allowed for a significant exchange of ideas and knowledge. In addition, Uthman is also known for organizing the official copying of the Qur'an to maintain the authenticity of Islam's sacred text. In the social realm, Uthman implemented policies that supported the welfare of Muslims, including distribution of zakat and economic empowerment. Although his reign brought prosperity, it also caused dissatisfaction among several groups, which ultimately contributed to the tragic event of Uthman's assassination. Overall, the period of Islamic civilization under the leadership of Uthman bin Affan reflected a period of progress in many aspects of life. The maintenance and development of the Al-Qur'an, territorial expansion, economic progress and social efforts have made a major contribution to the foundation of a strong and sustainable Islamic civilization.